Training for Reducing Academic Procrastination among University Students in Indonesia: A Literature Review - Teguh Dwi Putranto; Dwi Prasetyo (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Background: Academic procrastination experienced by university students not only hinders their plans to work immediately after graduation. If not handled immediately, academic procrastination can trigger serious problems, such as mental health problems in university students. This condition is certainly an obstacle that needs to be resolved so that it does not become a problem in the academic realm. Objective: To find out training to reduce academic procrastination among university students in Indonesia. Methods: This study uses a qualitative approach with the Literature Review method. The unit of analysis in this study is journal articles collected through a search process on